Study of MA0.7FA0.3PbI3 Based Perovskite Solar Cell - Sudhir Kumar; Dr. R. K. Verma (International Journal of Scientific Research in Science and Technology, 2025)
Perovskite solar cells (PSCs) bring a revolution in photovoltaic industry because of their easy manufacturing and high efficiency. PSCs have become very popular among researchers due to their desirable optical and electronic properties, such as tuneable band gap [1], large absorption coefficient [2], high charge carrier mobility [3], long diffusion lengths [4] and lower cost compared to conventional crystalline Si solar cells [5].The most investigated material in PSCs is MAPbI3 [6], however its thermal stability is also a source of worry due to volatile nature of organic cations. The low band gap (1.45 eV) of FAPbI3 attracts researchers since it is close to the Shockley-Queisser limit [7]. FAPbI3, on the other hand, contains a minor amount of yellow phase (δ-phase), which is unsuitable for long- term solar applications [8]. The lack of stability in FAPbI3 has hampered the development of FAPbI3-based PSC. However, while the PCE of PSCs is relatively good, these solar cells are extremely vulnerable to water due to the hydrophilic nature of organic cations. As a result, PSCs in an aquatic environment become unstable. These features prompted us to investigate perovskite materials with mixed cations.
Keywords: Provskite; Sollar Cell; MAPbI3; FAPbI3